Evaluation of Ascorbic Acid Content in Edible Leaves: A Comparative Study of Diverse Plant Species (International Journal of Scientific Research in Science and Technology, 2025)
Edible leaves are a rich source of vitamin C, an essential nutrient for immune function, collagen synthesis, and antioxidant defense. Moringa oleifera, Psidium guajava, and Phyllanthus emblica provide substantial amounts of vitamin C, supporting iron absorption and reducing the risk of chronic diseases. While citrus fruits are well-known sources, leafy greens offer an often-overlooked alternative. Cooking methods affect vitamin C retention, with steaming preserving more nutrients than boiling. Traditional diets have long recognized the benefits of leafy greens, emphasizing their role in preventing deficiencies and promoting overall health. Increased dietary inclusion of these leaves can enhance nutritional well-being.
Keywords: Edible leaves; Traditional diet; Vitamin C; Health benefits